Public participation in legislative process during the state of emergency in Vietnam - Thi My, Hanh Dang; Nguyen, Minh Tuan (Ius Humani. Jornal do direito, 2025)
This research attempts to comprehensively analyze the role and requirements of people's participation in the legislative process during Vietnam's state of emergency. Using conventional, trusted legal research methods, most notably desk review of legislation and case law analysis, this research affirms that, during a state of emergency, procedures involving public participation cannot follow the usual process. However, a pandemic must never be used as an excuse to erode democratic principles, and only when citizens actively take part in regular circumstances will they have the motivation to engage during emergencies. With Vietnam, many legal documents were issued by executive agencies instead of the National Assembly. Therefore, although the timely issuance of policies and laws was ensured during the pandemic, the principles of the legislative process were not fully upheld or implemented, leading to many debates regarding the legality of the documents issued during this period. In that sense, this research focuses on analyzing the current legal system and several typical cases of law enforcement in Vietnam and other countries to identify the legal gap and propose solutions to improve the legal framework on this issue in Vietnam.